توظيف التراث الشعبي في مسرح سعد الله ونوس الملحمي و تقنياته. (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
راودت فكرة استلهام التراث وتوظيفه كثيراً من المسرحيين العرب، وبقي الفرق بينهم في كيفية صياغة المادة التراثية وكيفية توظيفها. وتطلع سعد الله ونوس– مثل غيره من المسرحيين– إلى استلهام التراث واسترفاده في مسرحه، فأثرى مسرحه بمصادر تراثية متنوعة. وقد سعى إلى توظيف التراث انطلاقاً من مبدأين أساسيين:(الوعي بأبعاد التراث- الوعي بأبعاد الواقع)، وقد استدعى ذلك تحديداً لمفهوم التراث " لغوياً واصطلاحياً " بوصفه مفهوماً سيتكرر استخدامه في هذا المقال، ومن ثم بحث طرق توظيف ونوس للتراث وتقنياته في ذلك، ونظراً لاتساع مجال البحث في هذا الموضوع فقد تم تناول التراث الشعبي فقط "الحكاية الشعبية، الأمثال الشعبية، النكت الشعبية ". Using tradition in the theater was a new idea for many Arabian playwrights. The difference between them is how they use the traditional subject. Saad Allah Wanoos wanted to use tradition in his plays, so he enriched his theater and enhanced it with varied traditional resources. He used the traditional according to two principles (realization of tradition, realization of reality), so identifying tradition, which will be used many times in this article, becomes so necessary, then clarifying the method which was used by Wannos for using tradition and its techniques. Regarding the huge size and great scope of this subject, this research only concentrates on public tradition, "public lesson, public jokes, public story".